2013
DOI: 10.4028/www.scientific.net/msf.765.205
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Process Parameters on Twin Roll Cast Strip of the Alloy AZ31

Abstract: Reducing vehicle weight and emissions by lightweight design is a major goal of the automotive industry. Magnesium as the lightest structural metal offers a significant weight saving potential compared to steel and aluminium. Cast magnesium components are widely used, e.g. as engine blocks or gear box housings. The application of magnesium sheets is currently hampered by the low formability of magnesium which means that a large number of rolling passes is required to roll a DC cast slab to final gauge sheet. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…[4,12,13]. However, the relatively fast freezing tendency and wide freezing range of molten Mg alloys make it difficult to decrease the amount of mushy zones by controlling the above mentioned processing variables.…”
Section: Resultsmentioning
confidence: 97%
“…[4,12,13]. However, the relatively fast freezing tendency and wide freezing range of molten Mg alloys make it difficult to decrease the amount of mushy zones by controlling the above mentioned processing variables.…”
Section: Resultsmentioning
confidence: 97%
“…The microstructural evolution during warm rolling and subsequent annealing as well as the resulting tensile properties were analyzed and discussed. Kurz et al 6 studied the influence of process parameters on AZ31 TRC strip. It is found that optimization of process parameters of TRC offers the possibility to produce high quality sheet material.…”
mentioning
confidence: 99%
“…Initial results from these activities on conventional wrought and cast alloys have shown promising sheet properties [2][3][4][5][6]. Former results indicate that the processing parameters of twin roll casting have a significant influence on the microstructure and texture of the strips [7]. The degree of deformation in the strip depends on the position of the solidification front.…”
Section: Introductionmentioning
confidence: 98%